+0  
 
+2
260
1
avatar+104 

How do you rewrite this as of \(y=\text a x+\text b\)?

\(y - 3 = \frac1 2 x + 1\)

 Nov 28, 2017
 #1
avatar+95884 
+3

y - 3  = (1/2)x + 1      add 3 to both sides

 

y  = (1/2)x  +  4

 

 

cool cool cool

 Nov 28, 2017

8 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.